Gene Expression Signatures of Smoking and Acute Myocardial Infarction: A Blood Transcriptome Analysis - Fang-Fang Liu; Yi-Xuan Yan; Hong-Feng Zhang; Ke Li (Mediators of Inflammation)
Conclusions: Our findings suggest that gene expression changes induced by smoking in blood may contribute to the heightened risk of AMI. These identified genes are likely to play critical roles in the pathogenesis of AMI. Given the accessibility of peripheral blood samples, the expression levels of these genes could potentially serve as biomarkers for assessing cardiovascular health, particularly in individuals with a history of long-term exposure to cigarette smoke.